2012
DOI: 10.1186/1475-2840-11-100
|View full text |Cite
|
Sign up to set email alerts
|

GLUT4 content decreases along with insulin resistance and high levels of inflammatory markers in rats with metabolic syndrome

Abstract: BackgroundMetabolic syndrome is characterized by insulin resistance, which is closely related to GLUT4 content in insulin-sensitive tissues. Thus, we evaluated the GLUT4 expression, insulin resistance and inflammation, characteristics of the metabolic syndrome, in an experimental model.MethodsSpontaneously hypertensive neonate rats (18/group) were treated with monosodium glutamate (MetS) during 9 days, and compared with Wistar-Kyoto (C) and saline-treated SHR (H). Blood pressure (BP) and lipid levels, C-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 64 publications
(82 reference statements)
7
83
3
3
Order By: Relevance
“…A decrease in the gene and/or protein expression of IRS-1 with concomitant insulin resistance was observed in muscle biopsies of insulin-resistant Pima Indians (36), muscle of T2D subjects (33), and muscle biopsies from women with gestational diabetes (15). Similar concordance of mRNA gene expression of GLUT4 in the skeletal muscle of rats (41) and humans (15,33) and for GYS mRNA expression in the muscle of T2D subjects (72) and insulin resistance has been reported. The decline observed in GLUT4 and GYS1 gene expression in the diabetic animals during insulin deprivation (D Ϫ I) indicates decreased muscle insulin sensitivity, which was confirmed by the status of Akt-related signaling under acute insulin stimulation.…”
Section: Discussionmentioning
confidence: 59%
“…A decrease in the gene and/or protein expression of IRS-1 with concomitant insulin resistance was observed in muscle biopsies of insulin-resistant Pima Indians (36), muscle of T2D subjects (33), and muscle biopsies from women with gestational diabetes (15). Similar concordance of mRNA gene expression of GLUT4 in the skeletal muscle of rats (41) and humans (15,33) and for GYS mRNA expression in the muscle of T2D subjects (72) and insulin resistance has been reported. The decline observed in GLUT4 and GYS1 gene expression in the diabetic animals during insulin deprivation (D Ϫ I) indicates decreased muscle insulin sensitivity, which was confirmed by the status of Akt-related signaling under acute insulin stimulation.…”
Section: Discussionmentioning
confidence: 59%
“…Reduced GLUT4 expression is characteristic of insulin resistance in the heart (24,47) as well as in other insulinsensitive organs (16). It is detectable early after the onset of high-fat feeding in hearts from WT mice and is associated with reduced glucose uptake, even in the absence of impaired insulin signaling (47).…”
Section: Discussionmentioning
confidence: 99%
“…These data may suggest that insulin sensitivity is improved in HFD-fed Phd2 f/f /aP2-Cre mice compared with HFD-fed control mice. It is reported that Glut4 expression in skeletal muscle is suppressed in a rat model of insulin resistance, 31 suggesting that Glut4 upregulation in Phd2 f/f /aP2-Cre mice may be due to an improvement in insulin sensitivity. However, it is not clear how PHD2 deficiency in adipocytes affects the skeletal muscle insulin signaling pathway; further study is needed.…”
Section: Discussionmentioning
confidence: 99%